Intelijen Kejaksaan Perspektif Ketatanegaraan Indonesia dan Ketatanegaraan Islam - Tegar Mawang Ditha; Dian Ekawaty Ismail; Lusiana M. Tijow (Al-Mizan (e-Journal), 2020)
This article discusses the existence of prosecutorial intelligence which is reviewed in terms of the Indonesian constitutional structure and the Islamic state administration. This problem will be answered methodologically by using normative legal research, namely reviewing literature, laws and regulations and court decisions relating to the object of research. Based on the research results, the role of intelligence in Islamic history was an important factor in the movement to maintain the glory of Islam led by Muhammad. to fight the enemy of Islam. Intelligence activities get recognition from the content of several verses in the Koran as a way to practice amar ma’ruf nahi munkar. Meanwhile in the state administration in Indonesia, the prosecutor's intelligence activities as state intelligence administrators have an important role in maintaining state security and order in groups or individuals who want to destroy the order of life as a nation and state.